HUBUNGAN ANTARA PELAKSANAAN PIJAT BAYI DENGAN PERTUMBUHAN BERAT BADAN BAYI DI DESA MOJOJEJER KECAMATAN MOJOWARNO KABUPATEN JOMBANG - Ratnaningsih, Tri (JURNAL KEPERAWATAN BINA SEHAT, 2011)
Habit massage is a tradition that has been known since long, but many parents, especially mothers less in doing infant massage. The aim is to find out the relationship between the implementation of infant massage with your babys growth in Mojojejer Village, Mojowarno Jombang. The study design was cross sectional analytic. There are two research variable implementation of infant massage as an independent variable and infant growth as the dependent variable. The study population of all Mothers who have babies in Mojojejer Village Mojowarno Jombang were 112 mother infant. Samples were taken with a purposive sampling of 50 respondents. Data collected by questionnaire instrument (checklist) and then tested with Spearman rho test. Test results showed that p = 0.00, α = 0.05 then p <α So H0 rejected and H1 accepted means there is a relationship between the implementation of infant massage with your babys growth in Mojokeker Village District Mojowarno Jombang regency. The results of this study indicate that by doing good baby massage then respondents have created a safe and comfortable environment for babies due to the granting of the baby massage baby will instantly feel calm and can reduce the physiological changes in the human body. So, with variable conditions to stimulate accelerated growth of the baby. Conclusion The research indicates there are relation with the implementation of infant massage infant growth. Application of infant massage for infants can be done well if the mother can increase the knowledge about massage, which can be done through mass media or also follow the extension of health personnel with sufficient knowledge so that mothers can stimulate the growth and development of children one of them by doing a massage on the baby.Key word: Baby,baby massage, infant growth.